Still some way to go: institutionalisation of sustainability in German local governments. Issue 5 (4th May 2017) - Heinrichs, Harald; Schuster, Ferdinand
ABSTRACT: There is a widespread consensus among sustainability experts about the need for ambitious transformative practices in order for a sustainable development to progress. Agenda 21 emphasised the need for multilevel and multi-actor governance and explicitly focused on the local level. The conceptual and analytical preference of governance beyond government has directed attention towards the interaction between state and non-state actors. The present article focuses on the role of (local) state institutions in sustainability governance. We argue that an effective implementation of sustainability in government institutions is a precondition for a successful multi-stakeholder governance of a sustainable development. The guiding question of this article is: How has sustainability been institutionalised in local governments in Germany in the last 20 years after Agenda 21 was adopted? Based on a conceptual framework, we are presenting the empirical results of a survey of 371 German cities and municipalities in this article, which primarily aims at providing empirical evidence on to what extent sustainability has been institutionalised in German local governments. The article ends with discussing the potential reasons for the institutionalisation deficit observed and gives an outlook on the potential for developing a sustainability state, that is, a state dedicated to institutionalising sustainability.